The impact of competition on cost efficiency of insurance and takaful sectors: evidence from GCC markets based on the stochastic frontier analysis - Alshammari, Ahmad Alrazni; Syed Jaafar Alhabshi, Syed Musa; Saiti, Buerhan (Elsevier B.V, 2019)
In recent years, competition in the insurance sector has increased due to the number of players added by the emergence of takaful. This paper examines the impact of competition on the cost efficiency of conventional insurance and takaful sectors in Gulf Cooperation Council (GCC) countries between 2009–2016 using a stochastic frontier cost function. Overall, results suggest that the relationship between competition and efficiency is positive and supports the Quiet Life (QL) hypothesis where managers in a less competitive market may utilise the market power of their firms and reduce their efforts. However, importantly, there are differences between takaful operators and conventional insurers in this respect. The relationship between competition and efficiency turns out to be negative where conventional insurance is concerned, and positive only for takaful. The positive relationship between competition and cost efficiency may encourage policy makers and regulators to support a competitive insurance industry which should improve efficiency. However, they should be aware of the degree of competition and use restrictions and requirement for market entry carefully.